Speaking for the nation intellectuals and nation-building in the post-Yugoslav space - Sicurella, Federico Giulio (Discourse approaches to politics, society, and culture ;, 2020)
"The book explores the nexus of intellectual activity and nation-building from a critical discourse-analytical perspective. By examining how public intellectuals from Serbia, Croatia, and Bosnia and Herzegovina commented on key national events in editorials and opinion pieces, it offers unique insights into contemporary nation-building discourses in an enlarging Europe. Through a detailed reconstruction of the debates concerning the selected events, the book also provides fresh empirical evidence of the implications and challenges of post-socialist transition, post-conflict reconciliation, democratisation and European integration in the post-Yugoslav region. Its versatile framework, which innovatively combines sociological and linguistic approaches to the discursive positioning of intellectuals, may be readily applied to the analysis of intellectual engagement with current affairs and public life in general"--